Penggunaan Kulit Etak Dalam Bancuhan Konkrit Pengganti Simen - Zulkifli, Mohamad Zulfakry Aiman; Abdul Ghani, Abdul Halim (Recent Trends in Civil Engineering and Built Environment, 2022)
The use of concrete in construction is very widely used in buildings and infrastructure. Weaknesses in management and the authorities in managing the environment affect future generations. Materials such as shells are dumped in landfills. Therefore, in this study the use of etak shell as a substitute for cement. The objective of this study was to detail the workability and strength of concrete mixes of etak shell cement replacement. In addition, a highlight study was conducted on the use of shells as a cement substitute in concrete to identify the optimal percentage of use for density and compressive strength during the 28-day concrete curing time. For the study of the use of etak shell, four (4) types of blends were prepared for the mixture which showed that etak shell was 0%, 5%, 10% and 15%. A total of 24 concrete samples were produced for each test conducted within a curing time of 7 days. The tests performed include, concrete workability test, density test and compressive strength test. In the highlight study conducted, there were 9 articles that were referenced to obtain the optimal percentage for the shellfish mixture. The results of this study on the use of shells and the results of the study highlights the use of shells powder has the potential as a mixing material in concrete to improve the compressive strength and better disposal of shells can be reduced.